Sleep Quality, Perceived Stress and Body Mass Index in Adolescent College Students- Cross- Sectional Study - Saleem Ullah Abro, Adil Khan, Muhammad Saqib ur Rehman, Gati Ara, Qurratul Ain Saleem, Faisal Ali Baloch, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the sleep quality, perceived stress and body mass index in adolescent college students- a cross-sectional study. Methodology: It is a descriptive cross-sectional study, conducted in various aptitude training/Entrance test centers. The ERB of this study was taken from KM&DC in 2018 Karachi. The duration of the study was two months in 2021. The 498 students were enrolled, and intake of antipsychotic drugs was excluded from this study. The two scales (Pittsburgh Sleep Quality Index, and Perceived Stress Scale) and Body Mass Index were calculated as weight divided by height [kg/ m2]. For analysis, all qualitative variables were expressed as counts with percentages. Pearson Chi-Square test was used to check the association of perceived stress levels concerning studied baseline qualitative data sets. A P-value < 0.05 was considered statistically significant. Results: Mean values of sleep, perceived stress, body mass index, and age were 10.74±4.03, 21±10, 15.53±3.5 and 18±0.83 respectively. Poor sleep (96.3%), moderate level of stress (42.1%), and underweight (79.6%) were present in participants. Duration of sleep did not show a significant (>0.05) association with perceived stress and also mean perceived stress did not show a significant association (>0.05) with Sleeping Habits. Practical Implication: This study would be helpful for early diagnosing and early prevention of the effects of poor sleep and higher perceived stress levels on body mass index (underweight or obesity) in college students. Conclusion: Sleep disturbances, stress, and obesity can be predicted early and prevented or coped with early in students. Keywords: Adolescent, Body Mass Index, College Students, Obesity, Perceived Stress, Sleep Quality,sleep duration.